2018
DOI: 10.3389/fphar.2018.01350
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review on Zeolite Clinoptilolite Safety and Medical Applications in vivo

Abstract: Unique and outstanding physical and chemical properties of zeolite materials make them extremely useful in a variety of applications including agronomy, ecology, manufacturing, and industrial processes. Recently, a more specific application of one naturally occurring zeolite material, clinoptilolite, has been widely studied in veterinary and human medicine. Due to a number of positive effects on health, including detoxification properties, the usage of clinoptilolite-based products in vivo has increased enormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
129
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(159 citation statements)
references
References 115 publications
4
129
0
1
Order By: Relevance
“…Over the last years, a number of investigations were conducted to test the use of natural zeolites as low-cost adsorbents for the removal of heavy metals [9], salts [10], and ammonium ions [11]. Zeolite-based adsorbents have a unique crystalline microporous structure and high metal-binding capacity [12,13], and in some cases are suitable for detoxifying the body by consumption [14]. These minerals are characterized by a notably uniform pore structure with a molecular dimension <0.13 nm formed between tetrahedrally coordinated Si 4+ and Al 3+ that are connected via oxygen atoms [15].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, a number of investigations were conducted to test the use of natural zeolites as low-cost adsorbents for the removal of heavy metals [9], salts [10], and ammonium ions [11]. Zeolite-based adsorbents have a unique crystalline microporous structure and high metal-binding capacity [12,13], and in some cases are suitable for detoxifying the body by consumption [14]. These minerals are characterized by a notably uniform pore structure with a molecular dimension <0.13 nm formed between tetrahedrally coordinated Si 4+ and Al 3+ that are connected via oxygen atoms [15].…”
Section: Introductionmentioning
confidence: 99%
“…The apparent safety of zeolites compared with asbestos, despite both being silicate minerals, may be related to their physical structure. Whereas asbestos is a fibrous material, most zeolites have orthorhombic crystalline structures with accessible open channels for water and large ions . The safety of zeolites and, in particular, clinoptilolite, has been tested in animals and humans, by ingestion or injection .…”
Section: Discussionmentioning
confidence: 99%
“…The safety of zeolites and, in particular, clinoptilolite, has been tested in animals and humans, by ingestion or injection . The European Food Safety Authority panel on additives in animal feed (2013) reported that clinoptilolite was non‐toxic at doses of 10 000 mg/kg . An earlier comprehensive toxicology study used micronized clinoptilolite as a dietary supplement in rats and mice for up to one year, finding that doses of 1000 mg/mice/day elicited no apparent side effects or toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations